1995
DOI: 10.1002/1097-0142(19950415)75:8<2147::aid-cncr2820750818>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of c-erbB-2 in epithelial ovarian cancer. Prognostic value and relationship with response to chemotherapy

Abstract: Background. Overexpression of the c‐erbB‐2 protein has been reported in tumors from approximately 25% of patients with epithelial ovarian cancer. However, its clinical significance has not been well established. Methods. Overexpression of the c‐erbB‐2 protein was studied by immunohistochemistry in paraffin‐embedded tumor tissue from 106 patients with ovarian cancer. Results. Tumors from 23 patients (21.7%) had c‐erbB‐2 overexpression. The percentage of tumors with overexpression was higher in those with Stages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
48
1

Year Published

1998
1998
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(51 citation statements)
references
References 29 publications
2
48
1
Order By: Relevance
“…Thus far, c-erbB-2 overexpression, a frequent event in several human cancers, including breast tumors, has been correlated with a poor prognosis (Kern et al, 1994;Felip et al, 1995;Rilke et al, 1991;Slamon et al, 1989). In addition, in vitro studies have shown that transfection of p185 HER2 can induce proliferation and a malignant phenotype (Liu et al, 1995;Di Fiore et al, 1987).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus far, c-erbB-2 overexpression, a frequent event in several human cancers, including breast tumors, has been correlated with a poor prognosis (Kern et al, 1994;Felip et al, 1995;Rilke et al, 1991;Slamon et al, 1989). In addition, in vitro studies have shown that transfection of p185 HER2 can induce proliferation and a malignant phenotype (Liu et al, 1995;Di Fiore et al, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…In this pathway, the kinase cascade involves Raf, MEK and mitogen-activated protein kinase (MAPK). An association between overexpression of the 185 Kd c-erbB-2 encoded protein (p185 HER2 ) with both poor prognosis and decreased survival has been reported in breast, ovarian and non-small cell carcinomas (Kern et al, 1994;Felip et al, 1995;Rilke et al, 1991;Slamon et al, 1989). This association suggests that the deregulated expression of c-erbB-2 may have a profound e ect on the development and progression of certain tumors.…”
mentioning
confidence: 99%
“…43 In this regard, patients with tumors demonstrating overexpression of erbB-2 have a higher intrinsic resistance to conventional chemotherapeutic agents and a shortened relapse-free survival. 32,43 Moreover, breast cancer cell lines selected for multidrug resistance often overexpress erbB2 receptors. 28,29,33,34 Recognizing that erbB-2 plays a key role in tumor cell chemoresistance, several groups have employed strategies to modulate cell surface erbB-2 as a means to enhance the sensitivity of tumor cells to chemotherapeutic agents.…”
Section: Erbb-2mentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14] In addition, alterations in the expression of various oncogenes, such as Bcl-2, [15][16][17][18][19] p53, 18,[20][21][22] and cyclin D1, 23,24 and growth factor receptors, not only can lead to the perturbation of growth regulation but may also affect the sensitivity of tumor cells to conventional chemotherapy. [25][26][27][28][29][30][31][32][33][34] The delineation of some of the genetic determinants involved in drug resistance has enabled the development of new gene therapy-based strategies to overcome this important clinical problem.…”
Section: Introductionmentioning
confidence: 99%
“…Amplification and overexpression of HER-2 has been implicated in the pathogenesis of several human malignancies, including breast, ovarian and lung carcinomas (Slamon et al, 1989;Kern et al, 1994;Felip et al, 1995), and its overexpression correlates significantly with poor prognosis in subsets of patients with breast cancer (Slamon et al, 1987;Rilke et al, 1991;Pupa et al, 1996). In vitro studies using rodent cells indicated that p185 neu overexpression per se is sufficient to induce malignant transformation (Di Fiore et al, 1987).…”
mentioning
confidence: 99%